Decreasing delivery room intubations: A quality improvement project. (27th August 2021) - Jardine, Luke; Bates, Karina; Bates, Amanda; Muirhead, Renee; Bischoff, Elise; Sly, Angela; Cross, Tenille; Barrett, Jade; Newman, Tracey; Birch, Pita; Woodgate, Paul; Mausling, Richard; et al.
Abstract : Aim: The delivery room intubation rate for babies born less than 32 weeks postmenstrual age (PMA) at the Mater Mothers' Hospital in 2017 was 51%. Delivery room intubation of preterm infants may be associated with an increased risk of developing bronchopulmonary dysplasia. This quality improvement project aimed to decrease the rate of delivery room intubation for infants born less than 32 weeks PMA. Methods: A quality improvement process using the evidence‐based practice for improving quality framework and Plan‐Do‐Study‐Act cycles was undertaken from October 2018 to December 2019. Commencing bubble continuous positive airway pressure for initial resuscitation in the delivery room was the principal change idea. Results: The delivery room intubation rate for infants born less than 32 weeks PMA before the commencement of this project was 48% (cohort 1, n  = 221). There was a significant decrease in the rate to 37.2% while the project was being conducted (cohort 2, n  = 277) and a further significant reduction to 28.2% after introducing bubble continuous positive airway pressure in the delivery room (cohort 3, n  = 202). There was a significant improvement in admission temperatures and a significant decrease in mortality rate between cohort 1 and cohort 2 but not between cohort 2 and cohort 3. There was no change in the rate of discharge home on oxygen between cohorts. Conclusions: This quality improvement project led to a significantly decreased delivery room intubation rate in infants born less than 32 weeks PMA. There was no evidence of any adverse outcomes with this approach.